A companion to the works of Hermann Broch - Bartram, Graham, 1946-; McGaughey, Sarah; Tihanov, Galin (Studies in German literature, linguistics, and culture., 2019)
Hermann Broch (1886-1951) is best known for his two major modernist works, The Sleepwalkers (3 vols., 1930-1932) and The Death of Virgil (1945), which frame a lifetime of ethical, cultural, political, and social thought. A textile manufacturer by trade, Broch entered the literary scene late in life with an experimental view of the novel that strove towards totality and vividly depicted Europe's cultural disintegration. As fascism took over and Broch, a Viennese Jew, was forced into exile, his view of literature as transformative was challenged, but his commitment to presenting an ethical view of the crises of his time was unwavering. An important mentor and interlocutor for contemporaries such as Arendt and Canetti as well as a continued inspiration for contemporary authors, Broch wrote to better understand and shape the political and cultural conditions for a postfascist world. This volume covers the major literary works and constitutes the first comprehensive introduction in English to Broch's political, cultural, aesthetic, and philosophical writings.